A systematic review of policy approaches to dairy sector greenhouse gas (GHG) emission reduction. (20th January 2018) - York, L.; Heffernan, C.; Rymer, C.
Abstract: The dairy sector is a significant source of anthropogenic greenhouse gas (GHG) emissions. The increasingly robust emission inventories allow researchers to consider mitigation. However, there is a gap in knowledge regarding the extent to which mitigation research has been implemented as policy. The authors undertook a systematic a review of national-level dairy policy of 23 countries broadly following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocols. The aim of the study was to identify international trends in dairy sector GHG emission reduction policy. Sampled countries included the 12 countries with the highest quantity of dairy sector enteric methane emission and 11 Annex I countries with the largest number of dairy cattle per capita. A total of 34 documents were collated containing 62 policies across five themes. Themes included: nutrition, manure, health, breeding and management. Thirty-one policies were identified for both the high emission nations and Annex I nations with the largest number of dairy cattle per capita. Nutrition based interventions account for 36% (n = 11) of all policies identified for high emitting nations. Manure based interventions account for 48% (n = 15) of all policies identified for Annex I nations with the largest number of dairy cattle per capita. Across the sample, policymakers favoured manure management strategies (n = 24), particularly anaerobic digestion which accounted for 21% (n = 13) of all identified policies. Nutrition based mitigation strategies were also preferred (n = 17). Policies aimed at reducing sector size were largely ignored (n = 4). The results indicate that significant mitigation is unlikely as manure emissions are only a small portion of total dairy sector emissions. The study concludes that policymakers are selecting the less politically sensitive mitigation strategies at the cost of emission reduction. Highlights: Manure management was favoured by policymakers, particularly anaerobic digestion. Nutrition based mitigation strategies were also preferred. Policies aimed at reducing sector size were largely ignored. Significant mitigation is unlikely due to the focus on manure emissions. Less politically sensitive policies are selected at the cost of emission reduction.